A Lean Manufacturing Strategy and Its Role in Achieving the Competitive Advantage of the Organization An Exploratory Study On a Number of Industrial Companies in Zakho District / Duhok Governorate - Al-Jarjari, Khder Kh. (Humanities Journal of University of Zakho, 2018)
The research Address the subject of Lean manufacturing strategy as one of the modern topics that emerged as a result of the rapid developments in the world of business and the development of information systems and the spread of computers and the Internet in the world which is used in Management of production and service companies leading to increased efficiency of its administrative , and here companies realized the need to go to apply the Lean manufacturing in their work and use its benefit , most notably the elimination of waste and loss in production processes and thus reduce production costs , Achieving survive and thus achieve competitive advantages and superiority over competitors . A group of four industrial companies have been chosen to be the field in which the practical part would be done. The researcher has depended on the questionnaire as a main tool to collect the data and the information in the practical part of the study, To achieve the aims of the study and to test the hypotheses of the study, a hypothetical model has been designed to show the nature of the relationship between the variables in the study. Depending on the description and the specification of the variables in this study and testing the correlation relationships and the impact, a set of conclusions have been reached. The most prominent conclusions are there is a positive significant correlation relationship and significant impact relationship among the lean manufacturing methods and the competitive advantage in all the examined companies. Depending on the conclusions that have been reached by the researcher, the study presents a number of suggestions, notably the need to adopt the philosophy of lean manufacturing to enhance the achievement of the competitive advantage of companies surveyed.